New Drugs on the Internet: The Case of Camfetamine - Cinosi, Eduardo (Hindawi Publishing Corporation, 2014)
Introduction. The number of new psychoactive substances (NPS) advertised for sale online is constantly increasing and it has become a phenomenon of global concern. Among NPS, Camfetamine has been rediscovered as recreational drug in 2011. Very little information is still available in the scientific literature on its nature and potential health risks. Methods. Data in scientific literature were integrated with a multilingual qualitative assessment of a range of online resources over the period of 32 months (May 2011–January 2014). Results. N-Methyl-3-phenyl-norbornan-2-amine (Camfetamine) may act as an indirect dopaminergic agonist in the central nervous system and may have mild-moderate opioid activity too. There are no current epidemiological data about recreational use of Camfetamine; our research shows that it is indeed used especially by individuals with a history of recreational polydrug misuse. It facilitates mental alertness, induces relaxation, and, unlike many other stimulants, seems not to be associated with severe physical effects. Valid causes for concern issued in our research may be Camfetamine intravenous or intramuscular administration as well as its use in conjunction with other psychoactive substances. Conclusions. It is here highlighted that more large-scale studies need to be carried out to confirm and better describe both the extent of Camfetamine misuse and possible psychotropic/adverse effects.